Carpal Coalition: A Review of Current Knowledge and Report of a Single Institution's Experience with Asymptomatic Intercarpal Fusion. (June 2013) - DeFazio, Michael V.; Cousins, Benjamin J.; Miversuski, Roberto Augusto; Cardoso, Roy
Background: Carpal coalition is a relatively common, yet poorly recognized, anomaly that may present independently or in association with syndromic or metabolic disorders. While largely asymptomatic, symptoms may manifest secondary to biomechanical stress at the site of fusion. The purpose of this report is to describe 103 cases of carpal synostosis and provide a review of the etiology, classification, and clinical significance of intercarpal fusion. Method: Retrospective review of medical and radiographic records was conducted on all patients with identified carpal coalitions, between 2008 and 2012, at our institution. Demographic and historical data regarding trauma, infection, documented joint disease, and prior wrist symptomatology were analyzed for each case, and radiographic evaluation of carpal alignment was performed. Results: A total of 103 cases of carpal coalition, among 85 individuals, were reviewed. All cases presented asymptomatically with the highest proportion noted among individuals of African-Caribbean descent. The most frequent variant in our study population was lunate–triquetral coalition, which was present in 92 of the 103 identified cases. None of the cases evaluated in this study demonstrated clinical or radiographic evidence of carpal mal-alignment or instability. Conclusion: The results of our investigation demonstrate that carpal coalition presented most frequently among individuals of African-Caribbean descent. While the prevalence of this condition has yet to be studied specifically in Hispanic and African-Caribbean populations, our findings may reflect the genetic linkage between these and certain West African populations. To our knowledge, this represents the largest clinical series of carpal coalition in the English literature.